(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Intrusion Detection System is the process of intelligently monitoring the events occurring in a computer system or network, analyzing them for signs of violations of a security policy. Its primary aim is to protect the availability, confidentiality and integrity of critical networked information systems. This paper considered and reviewed a CAPTCHA based intrusion detection model. A method of incorporating signature was used along with the CAPTCHA in the intrusion detection model to clear the controversy identified in the existing model. The signature provides a means of identifying intruders that are able to by-pass the system as legitimate users. The model was implemented using a website hosted online. Dataset obtained from the site was analyzed based on NaÃ¯ve Bayes classification model using confusion matrices. Implementation of the data analysis was carried out using RStudio software package. Analyzed results shows a better Detection Rate (DR), Accuracy (CR) and False Positive Rate (FPR). This shows that the developed system has significant capability of identifying intelligent spywares targeted at breaking CAPTCHA